Agritouch- An efficient smartphone based approach for rooftop gardening - Islam, Muhaimenul; Shahriar, Fahmid (Recent Research in Science and Technology, 2020)
With the increasing growth of population in mega cities like Dhaka, most of the Agricultural land has given away for housing, factories, highways and other urban needs. As a result, lack of crop production as well as various environmental crisis has already been showing up with a great threat to humankind. Rooftop gardening can be an effective method to reduce this problem and the nutritional needs of the inhabitants. But for the unavailability of the necessary resources, supports and lack of awareness among the people, most of the spaces available at the rooftop are being unutilized. We have proposed an online and smartphone-based approach to overcome the above limitations. Though the current popularity of smartphones causes rising of different mobile application technologies and selecting the appropriate one could be challenging. Here we have introduced some latest technology stack that fit best to develop our application with a comparative study of the suitable geo-location-based services. AgriTouch, a smartphone app, will act as a bridge between the gardeners and the service providers to maintain the balance of nature.